Implications of Illegal Sea Fence Construction on Maritime Security, Environment, And Welfare Of Coastal Communities - Aygy Yolanda, Hariyantana; Sudiarso, Aries; Jhandana, I.B Putra (ARRUS Journal of Social Sciences and Humanities, 2025)
This study aims to analyze the implications of the construction of the sea fence on maritime security, the environment, and the welfare of coastal communities. The research method used is qualitative with a descriptive-analytical approach, utilizing secondary data from legal documents, official reports, scientific articles, and reliable news. The results of the study show that this sea fence violates various national regulations, such as the Regulation of the Minister of Marine Affairs and Fisheries No. 28 of 2021 concerning KKPRL, Law No. 27 of 2007 concerning the Management of Coastal Areas and Small Islands, and Law No. 32 of 2009 concerning Environmental Protection. The ecological impacts are also significant, including the destruction of mangroves and marine biota habitats that threaten the sustainability of coastal ecosystems. There are indications of a conflict of interest related to this project, which allegedly involves a large property developer for reclamation without transparency and participation of local communities. Weak coordination between government agencies such as the KKP, TNI AL, and Bakamla RI has also exacerbated this situation. The construction of illegal sea fences not only harms coastal communities economically and socially, but also violates the law and threatens the sustainability of marine ecosystems. Concrete measures such as the dismantling of illegal sea fences, rehabilitation of coastal ecosystems, increased coordination between agencies, and the implementation of sustainability-based policies are needed to prevent similar cases in the future.